COVID 19: Growth analysis, similarity study with HIV and its prevention through flavone rich natural foods - Jayshree Sadhukhan; Arijit Pan (Global Journal of Infectious Diseases and Clinical Research - Peertechz Publications, 2020)
COVID 19: Coronavirus Disease 2019; WHO: World Health Organization; CoV: Coronavirus; R2 value: Coefficient of Determination Value; HIV: Human Immunodeficiency Virus; DNA: Deoxyribonucleic Acid; RNA: Ribonucleic Acid; 2019-nCoV: 2019 novel Coronavirus; Tat: Transactivator of Transcription; SARS: Severe Acute Respiratory Syndrome, H0: null Hypothesis; H1: Alternate Hypothesis